The Impact of Economic Diversification on Foreign Direct Investment in the Kingdom of Saudi Arabia - Ayed, Fahim (Journal of Legal Sciences, 2025)
The Kingdom of Saudi Arabia has created the economic climate, diversified its economy, encouraged the private sector and worked to increase its contribution to the economic field, and established many incentives and guarantees to increase foreign direct investment flows. The study was divided into three main sections, preceded by an introduction and followed by results and recommendations. The first section dealt with the nature of economic diversification, its types, justifications, and goals in two topics. The first topic is entitled defining economic diversification and its types. The second topic is about the goals and justifications for economic diversification, and then the second topic is about the nature of foreign investment, its types, goals, and importance in light of Vision 2030. The first topic was entitled the concept of foreign investment, its types and objectives, the second topic was the incentives and obstacles to foreign investment in light of Vision 2030, and the third topic dealt with the impact of economic diversification on the development of foreign investment in Saudi Arabia. In two demands, the first entitled the relationship of foreign investment to economic diversification and the Public Investment Fund, and the second demand to increase economic diversification and develop the volume of foreign investment in Saudi Arabia.